Radar cross section - Knott, Eugene F.; Shaeffer, John F.; Tuley, Michael T. (Raleigh, NC SciTech Publishing, 2004)
This book is organized into five groups of chapters. Chapters 1 and 2 contain background information; Chapters 3 through 5 introduce the concept of scattering and present useful RCS prediction techniques; Chapter 6 displays examples of RCS behavior for simple and complex bodies; Chapters 7 through 9 address radar cross section reduction methods; Chapters 10 through 13 discuss techniques for measuring absorber properties and the scattering characteristics of test targets; and Chapter 14 examines practical ways to identify scattering mechanisms on complex targets.
Electronic reproduction.
Keywords: Radar; Radar cross sections; Electronic books